The Influence of Emotional Intelligence, Self Efficacy, and Employee Engagement on Employee Commitment in Digital Sector - Andreas Wijaya; Sophia Reni Susilo; Alfaro Diaz; Enjelio Abelto (Dinasti International Journal of Education Management And Social Science, 2024)
This study examines the impact of Emotional Intelligence, Self-Efficacy, and Employee Engagement on Organizational Commitment among employees in digital companies, utilizing data from 147 respondents. Emotional Intelligence significantly enhances Organizational Commitment through Employee Involvement. Employees with high EI are better at building strong interpersonal relationships and communicating effectively, which leads to higher levels of involvement and commitment to the organization. This is supported by the mediation effect found between EI and Organizational Commitment, emphasizing the importance of employee involvement. Self-Efficacy also positively influences Organizational Commitment through its effect on Employee Involvement. Employees with high self-efficacy are more confident and involved in their work, resulting in greater attachment and commitment to their organization. Direct relationships were found between Emotional Intelligence and Employee Involvement, indicating that higher EI leads to increased engagement and proactive behavior in the workplace. This further contributes to better job performance and organizational commitment. Additionally, Employee Involvement significantly enhances Organizational Commitment. However, Self-Efficacy does not have a significant direct impact on Employee Involvement, suggesting that other factors, such as organizational culture or leadership style, might play a more crucial role. Overall, fostering Emotional Intelligence and self-efficacy is essential for enhancing Employee Engagement and Organizational Commitment in digital companies.